(untitled) (KYAMC Journal, 2017)
Background: Femoral neck fractures are common in the elderly population. To avoid the poor outcome of internal fixation and for early mobilization, hemiarthroplasty is performed. However, there is inadequate evidence to support the choice between unipolar or bipolar hemiarthroplasty. Objectives: The aim of this study was to compare the outcome of unipolar with the bipolar prosthesis in geriatric patients. Methods: Forty-one patients above 60 years of age and an acute displaced fracture of the femoral neck were randomly allocated to treatment by either unipolar or bipolar hemiarthroplasty, in the Department of Orthopaedics at Khwaja Yunus Ali Medical College and Hospital, Enayetpur, Sirajgonj, Bangladesh in between December 2014 and February 2017. Functional outcome was assessed and compared using Harris hip score and radiological parameters with a follow-up of one year. Results: The two groups of patients with mean age of 67.3 in bipolar group and 75.6 in unipolar group did not differ in their pre-injury characteristics and perioperative parameters. The mean Harris hip score in bipolar and unipolar groups was 86.18±12.18 and 79.79±15.55, respectively (p=0.183); range of motion was 210.63±28.39 and 181.58±37(p=0.015) with bipolar and unipolar groups, respectively. Functional activities were better in the bipolar group. Complications like painful hip, posterior dislocation, periprosthetic fracture and acetabular erosion were encountered in unipolar prostheses. Conclusion: The use of bipolar endoprosthesis in the management of displaced femoral neck fractures in the elderly was associated with better mean Harris hip score and incidence of complications was limited. Hence, bipolar would be a better option in elderly patients with fracture neck of femur. KYAMC Journal Vol. 8, No.-1, Jul 2017, Page 10-14